2011
DOI: 10.1016/j.rvsc.2010.07.007
|View full text |Cite
|
Sign up to set email alerts
|

In vitro development of primordial follicles after long-term culture of goat ovarian tissue

Abstract: This study aims to investigate the effects of follicle stimulating hormone (FSH) and fibroblast growth factor-2 (FGF-2) on the survival and growth of caprine preantral follicles. Ovarian tissues were cultured for 1, 7, 14, 21 or 28 days in medium supplemented with FSH (FSH-2d or FSH-7d, i.e., with replacement of the culture medium every 2 or 7 days, respectively) or FSH + FGF-2 (replacement of the medium every 2 days). Non-cultured (control) and cultured ovarian fragments were processed for histological and ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 47 publications
0
5
0
2
Order By: Relevance
“…Although both FSH and EGF stimulated an increase in oocyte and follicle size in intermediate and primary follicles in 5 days culture, no effect on proliferation or viability of follicles was observed in response to the treatment. Recently it has been suggested that FSH might act indirectly on the PF through paracrine factors secreted by large follicles or stromal cells [10]. This argument however remains unclear since FSH acts as a survival factor despite absence of large follicles in the cortical tissue pieces.…”
Section: Introductionmentioning
confidence: 99%
“…Although both FSH and EGF stimulated an increase in oocyte and follicle size in intermediate and primary follicles in 5 days culture, no effect on proliferation or viability of follicles was observed in response to the treatment. Recently it has been suggested that FSH might act indirectly on the PF through paracrine factors secreted by large follicles or stromal cells [10]. This argument however remains unclear since FSH acts as a survival factor despite absence of large follicles in the cortical tissue pieces.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, additive effects on follicular growth (increase in diameter and higher daily growth rate) were observed when supplemented M. nigra extract was used in combination with FSH. The main functions triggered by FSH in the mammalian ovary in vitro include the maintenance of follicle survival (Adriaens, Cortvrindt, & Smitz, ; Matos et al., ), apoptosis prevention (Yang & Rajamahendran, ), antrum formation (Barros et al., ; Cecconi et al., ), follicular growth (Saraiva et al., ), cell proliferation (Adriaens et al., ), steroidogenesis (Shimada & Terada, ) and regulation of other genes (Kawashima et al., ). Therefore, it can be suggested that the interaction among the natural compounds of the M. nigra extract, supplements and FSH is required for the growth of oocytes from secondary follicles in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of follicle stimulating hormone (FSH) and FGF-2 in ovarian tissue culture has shown the promotory effects of FSH on percentage of the primary follicles. FSH alone or combined with FGF-2 increased the growth and integrity of caprine preantral follicle [45]. In cattle, FSH in combination of GDF-9 or bFGF has increased the rate of normal follicles and decreased the rate of apoptotic cells [46].…”
Section: Hormones and Growth Factors In Tissue Culturementioning
confidence: 96%